Pemerintahan Desa Pakramandan Desa Dinas Pedungan (Studi Harmonisasi Masyarakat Desa) - Trisna Sugiarti, Ni Kadek; Suka Arjawa, I.G. Putu Bagus; Kebayantini, Ni Luh Nyoman (JURNAL ILMIAH SOSIOLOGI (SOROT), 2017)
The village administration consists of Pakramanand village official who has long been known in Bali. Two village administration system that has become a tradition in Balinese life since the days of empire to the present. Pakramanis a traditional community with a focus on functionality in the areas of customs and Hinduism, a territorial unit whose members jointly implement social and religious activities were organized by a cultural system. Village Office is a village with a system of government where the agency is an extension of the central government. Harmonization is a thing or a state of harmony or harmonious. Village Pedungan one area that has two village administration system that is Pakramanand the village of Dinas Pedungan to have 14 custom banjar and banjar services. Pakramanwork patterns and village offices Pedungan an impact on the social life of the community. This study was analyzed using the concept of leadership of Max Weber's theory of bureaucracy with qualitative descriptive method using in-depth interviews and observation. This study shows the results stating that the existence of two systems of government do not cause problems to breakdown all can run in parallel and for their communication that harmony between all the elements that are inside. Keywords: Village Administration Pakraman, Village Office, Harmonization